PRIMARY PTERYGIUM EXCISION WITH CONJUNTIVAL AUTOGRAFT USING SUTURE VS AUTOLOGOUS BLOOD (Journal of Medical & Health Sciences Review, 2025)
Background: Pterygium surgery often requires conjunctival autograft fixation to reduce recurrence and complications. Traditional suturing techniques provide stability but are associated with postoperative discomfort, while autologous blood fixation offers a suture-free alternative with potential benefits in patient comfort and reduced inflammation.Objective: To compare the postoperative outcomes of conjunctival autograft fixation using sutures versus autologous blood in primary pterygium surgery. Materials and Methods: This prospective study was conducted at Khyber medical college Peshawar from December 2023 to December 2024. A total of 60 patients with primary pterygium were enrolled and divided equally into two groups: Group A (suture fixation) and Group B (autologous blood fixation). Outcomes assessed included conjunctival inflammation, granuloma formation, graft retraction, anatomical success, and functional success. Statistical analysis was performed to identify significant differences between groups.Results: Both groups achieved high anatomical success (90%) and functional success rates (Group A: 93.3%, Group B: 83.3%, p = 0.228). Granuloma formation was significantly higher in the suture group (20% vs. 3.3%, p = 0.044), while graft retraction was more common in the autologous blood group (23.3% vs. 3.3%, p = 0.023). Conjunctival inflammation and foreignbody sensation were comparable between groups, with no significant differences observed.Conclusion: Both techniques are effective for conjunctival autograft fixation in primary pterygium surgery, with distinct profiles of complications. Autologous blood offers reduced granuloma formation and postoperative discomfort, while sutures provide superior graft stability.